Preparation and Evaluation of Pralidoxime-Loaded PLGA Nanoparticles as Potential Carriers of the Drug across the Blood Brain Barrier. (18th October 2015) - Chigumira, Washington; Maposa, Prosper; Gadaga, Louis L.; Dube, Admire; Tagwireyi, Dexter; Maponga, Charles C.
Abstract : Pralidoxime is an organophosphate antidote with poor central nervous system distribution due to a high polarity. In the present study, pralidoxime-loaded poly(lactic-co-glycolic acid) nanoparticles were prepared and evaluated as a potential delivery system of the drug into the central nervous system. The nanoparticles were prepared using double emulsion solvent evaporation method. Poly(lactic-co-glycolic acid) (PLGA) in ethyl acetate made the organic phase and pralidoxime in water made the aqueous phase. The system was stabilized by polyvinyl alcohol. Different drug/polymer ratios were used (1 : 1, 1 : 2, and 1 : 4) and the fabricated particles were characterized for encapsulation efficiency using UV-VIS Spectroscopy; particle size distribution, polydispersity index, and zeta potential using photon correlation spectroscopy; and in vitro drug release profile using UV-VIS Spectroscopy. Mean particle sizes were 386.6 nm, 304.7 nm, and 322.8 nm, encapsulation efficiency was 28.58%, 51.91%, and 68.78%, and zeta potential was 5.04 mV, 3.31 mV, and 5.98 mV for particles with drug/polymer ratios 1 : 1, 1 : 2, and 1 : 4, respectively. In vitro drug release profile changed from biphasic to monobasic as the drug/polymer ratio decreased from 1 : 1 to 1 : 4. Stable pralidoxime-loaded PLGA nanoparticles were produced using double emulsion solvent evaporation techniques.